Gay Seouls: Expanding Religious Spaces for Non-Heterosexuals in South Korea. Issue 11 (19th September 2018) - Yi, Joseph; Jung, Gowoon; Segura, Saul Serna; Phillips, Joe; Park, Jerry Z.
ABSTRACT: What Protestant congregations offer spaces for worship and dialogue among persons with different sexual orientations? The academic literature finds or assumes that non-heterosexuals are stigmatized or invisible in theologically conservative congregations and are welcomed in progressive, affirming congregations. This article develops an alternative claim that some conservative or evangelical congregations offer attractive spaces for non-heterosexuals to worship and dialogue. We illustrate with an exploratory study of four congregations in South Korea—two theologically progressive, two evangelical—whose pastors welcomed everybody regardless of sexual orientation or gender identity. The "inclusive-evangelical" congregations retained conservative theology on sexuality (sexual relations only within heterosexual marriage) but offered more empathic dialogue with non-heterosexuals than did most evangelical congregations; they also provided more resources, conventional religious culture, and ties to traditional affective networks than the affirming-progressive congregations. Inclusive-evangelical congregations offer an institutional venue for non-heterosexual Christians in Korea to potentially reconcile three central values: conservative Christianity, traditional (Confucian) affective networks, and expressive individualism.